Off-pump versus on-pump coronary artery bypass procedures: postoperative renal complications in an Asian population - Loganathan, Sivakkanan; Nieh, C. C.; Emmert, M. Y.; Woitek, F.; Martinez, E. C.; Muecke, S.; Lee, C. N.; Kofidis, T. (Annals, 2010)
Diabetes and habitual smoking cause advanced coronary artery disease (CAD) in Asian patients at a younger age. No definite data exist as to whether off-pump (OPCAB) is better than conventional on-pump coronary artery bypass grafting (CCAB) in terms of postoperative renal complications. Thus, we aimed to compare the renal outcomes of on-pump and off-pump coronary artery bypass grafting (CABG) on our patients, which constituted a predominantly Asian population.
Der Download-Link funktioniert nur auf der Homepage der Universität Zürich
Gesehen am 29.03.2023